Pengaruh Pendekatan Open-Ended Terhadap Keterampilan Berfikir Kreatif dan Kemampuan Pemecahan Masalah Matematis di Sekolah Dasar - Febriani, Rindang; Syarifuddin, Hendra; Marlina, Marlina (Universitas Pahlawan Tuanku Tambusai, 2021)
Learning is the activity of the teacher in designing teaching materials so that the learning process can take place effectively, that is, students can learn effectively and meaningfully. Learning is an activity to train students' creative thinking skills. Creative thinking skills are skills that students must have in sorting and gathering information or answers to the questions addressed. In addition to creative thinking skills, students must also have the ability to solve problems systematically. The ability to systematically solve problems is needed to translate any problems that students find so that solutions can be found or solutions. This can be done by the teacher using a learning approach. One of them is the open-ended approach. The open-ended approach is a learning approach that presents a problem that has more than one problem solving truth, so that it can provide opportunities for students to gain knowledge and experience in solving problems in a variety of different ways. So that in the learning process using this approach, students can have creative thinking skills and the ability to solve problems systematically.